Relación entre dislipidemias y diabetes mellitus tipo 2 en adultos mayores en el Hospital General IESS-Babahoyo. Octubre 2024 - mayo 2025. - Melo Recalde, Sandra Maribel (2025)
Dyslipidemias occur when there are high levels of cholesterol, triglycerides, HDL and LDL cholesterol in the blood. This is due to poor diet, lack of exercise, and sometimes due to genetic alterations. Older adults with type 2 diabetes mellitus tend to suffer from these lipid disorders, which are a highly detrimental risk factor for the study population, as they may present cardiovascular diseases. The objective of the research was to determine the relationship between dyslipidemias and older adults with type 2 diabetes mellitus at the IESS Babahoyo General Hospital. This is a descriptive, quantitative, prospective, and cross-sectional study. The sample consisted of 80 older adults with type 2 diabetes mellitus. The results obtained an egalitarian study population. Biochemical data showed greater alterations in triglyceride levels, and a low nutritional status was present according to the older adult body mass index. It was concluded that physical inactivity in the study population can be attributed to various factors, such as physical limitations. The study proposal was conducted to identify the population's eating habits and nutritional knowledge. The food frequency survey revealed a positive response regarding the adoption of healthy eating habits; however, a significant prevalence of unhealthy food consumption was also observed.